Visible light induced nano copper catalyzed one pot synthesis of novel quinoline bejeweled thiobarbiturates as potential hypoglycemic agents. (25th April 2021) - Angajala, Gangadhara; Aruna, Valmiki; Subashini, Radhakrishnan
Abstract: An efficient visible light induced one pot three component approach for the synthesis of new quinoline bejeweled thiobarbiturates via Knoevenagel condensation and N ‐alkylation using copper nanoparticles (CuNPs) have been reported. These copper nanoparticles due to their diverse properties, smaller size (50–100 nm), and high surface area to volume ratio exhibit promising features for the reaction response such as the shorter reaction time, simple work‐up procedure, clean reaction profiles, and excellent product yields through reusability of the catalyst upto five cycles. The recovered catalyst was successfully characterized by EDAX and AFM analysis. In silico molecular docking studies were carried out to find out the effective binding affinity of the synthesized quinoline derivatives toward PPARγ protein. The results obtained showed that compounds 4d, 4e, and 4f possess good binding interaction toward PPARγ with binding energy of −7.4, −7.2 and, −7.6 k.cal/mol which was greater than standard rosiglitazone (−6.4 k.cal/mol) and comparable to that of standard pioglitazone (−7.9 k.cal/mol). In vitro α‐amylase and α‐glucosidase assays were performed for hypoglycemic activity evaluation. The compounds 4e and 4f at a concentration of 100 μg/ml showed 82.13% and 83.26% inhibition toward α‐glucosidase, 78.30% and 84.18% inhibition toward α‐amylase which was higher than standard pioglitazone and on par to that of rosiglitazone and acarbose. Abstract :